Differences in Consumer Attitudes in the Decision to Purchase Toyota Brand Cars and Honda Brand Cars in Banda Aceh City - Fahmi, IJal; Hamdani, Hamdani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Attitudes play an important role in making marketing decisions and there is a tendency to consider attitudes as the most important factor in predicting future behavior and can help companies predict product demand. Products and develop appropriate marketing programs a person's attitude toward product attributes may vary depending on beliefs and evaluations about product attributes in addition, there are other factors that also influence and will ultimately determine their interest in purchasing the product. Explore and analyze consumer attitudes toward the attributes and prices of Toyota and Honda branded automotive products to explore and analyze differences in consumer attitudes toward the attributes and prices of Toyota and Honda branded automobile products to obtain information and data for this research, the author conducted field research, specifically research on buyers/users of passenger cars), Toyota brand cars and passenger cars. Honda brand car the research object is the difference in consumer attitudes in deciding to buy Toyota brand cars and Honda brand cars in Banda Aceh city. Research results show that there is no significant difference in consumers' attitudes towards buying Honda or Toyota cars as shown by the Sig value t for all attitude attributes towards the studied car products are > α = 0.05 (The test results show that on average, the two research groups have similar attitudes towards buying cars Honda or Toyota brands) Attitude of consumers using Honda and Toyota cars Toyota considers the attributes of color, style, engine performance, after-sales service, engine and warranty the main consideration is most evident in the price attribute. in other words, the attribute used as a variable has overall positive attributes, but the price attribute has the highest positive attitude value compared to other attributes, for both Honda brand cars and Toyota brand.